Stereoselective Transesterification of P‐Chirogenic Hydroxybinaphthyl Phosphinates - Akari Kawajiri; Dr. Taro Udagawa; Prof. Dr. Mao Minoura; Prof. Dr. Toshiaki Murai (ChemistryOpen, 2022)
Abstract The substitution reaction of phosphinates with a binaphthyloxy group at the phosphorus atom with lithium alkoxides proceeded with good to high efficiencies to give P‐chirogenic phosphinates with a high enantiomeric ratio. As alcohols, primary, secondary, and tertiary alcohols could be used, and the use of tert‐butyl alcohol yielded the products with a higher enantiomeric ratio. A substrate with two different alkyl groups on the phosphorus atom could also participate in the substitution reaction to give the corresponding products in good yields with excellent selectivity. The molecular structures of one of the substrates and the corresponding products, determined by X‐ray analyses, proved that the substitution reaction at the phosphorus atom proceeded with inversion of the absolute configuration. The usefulness of the reaction was demonstrated by using it to prepare a drug candidate for Duchenne muscular dystrophy. Finally, thionation of the resulting phosphinates was carried out to form P‐chirogenic phosphinothioates.